Pengaruh Ball Peening terhadap Kekerasan Baja Tahan Karat AISI 316L - Widodo, Teguh Dwi; Raharjo, Rudianto (Rekayasa Mesin, 2016)
In this work, ball peening was performed in order to evaluate its effect on the AISI 316L hardness. The process was conducted by employing AISI E52100 Chrome Steel ball which has hardness 752 HVN as bomber. In this research ball peening process was performed at three different nozzle pressure (6, 7, and 8 bar) for 5 minutes. Vickers Micro Hardness Tester and Digital Optical Microscope was used to characterize the samples hardness and grains structure respectively. The results showed that the hardness of AISI 316L was improved. It may due to plastic deformation which toke places on its grains.